The Influence of Price, Product Quality, and Service Quality on Customer Satisfaction at Home Smart Rantauprapat - Lia Safitri; Zulkifli Musannip Efendi Siregar; Mulya Rafika (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
Consumer satisfaction is an important element that must be created by all types of businesses. Researchers also agree that consumer satisfaction is a prerequisite for gaining loyalty from consumers, consumer loyalty that can make consumers come to buy products sold by sellers. The purpose of this study was to examine the effect of independent variables consisting of price, product quality, and service quality on consumer satisfaction who have shopped at Home Smart Rantauprapat. This study uses a quantitative approach, collecting data using a purposive sampling method, which means that researchers apply specific criteria in determining which respondents can be sampled in this study. The number of samples used in this study was 100 people with the specified criteria being consumers who had shopped at Home Smart Rantauprapat and were 18 years and over, which aims to get valid answers. The results of this study indicate that price has a positive and significant effect on customer satisfaction at Home Smart Rantauprapat, product quality is proven to have a positive effect on customer satisfaction at Home Smart Rantauprapat and the last variable, namely service quality, is also found to have a positive and significant effect on customer satisfaction that has been shopping at Home Smart Rantauprapat.